Use of UV-C Treatments to Maintain Quality and Extend the Shelf Life of Green Fresh-cut Bell Pepper (Capsicum annuum L.) - Rodoni, Luis Maria (2011)
The objective of this work was to select a ultraviolet (UV-C) treatment for fresh-cut mature green bell pepper, and to evaluate the effect of its combination with refrigeration on quality maintenance. Bell pepper sticks were treated with 0, 3, 10, or 20 kJ/m2 UV-C in the outer (O), inner (I), or both sides of the pericarp (I/O) and stored for 8 d at 10 ºC. During the first 5 d of storage, all UV-C treatments reduced deterioration as compared to the control. The treatment with 20 kJ/m2 I/O was the most effective to reduce deterioration, and was used for further evaluations. In a second group of experiments, mature green bell pepper sticks were treated with 20 kJ/m2 I/O, stored at 5 ºC for 7 or 12 d and assessed for physical and chemical analysis, and microbiological quality. UV-C-treated fruit showed lower exudates and shriveling than the control. UV exposure also reduced decay, tissue damage, and electrolyte leakage. After 12 d at 5 ºC, UV-C irradiated peppers remained firmer and had higher resistance to deformation than the control. The UV-C treatments also reduced weight loss and pectin solubilization. UV-C exposure decreased the counts of mesophile bacteria and molds, and did not affect acidity or sugars. UV-C-treated fruit stored for 0 or 7 d at 5 ºC did not show major differences in antioxidants from the control as measured against DPPH or ABTS radicals. Results suggest that UV-C exposure is useful to maintain quality of refrigerated fresh-cut green pepper.